A new interpretation for the degradation phenomenon of ZnO varistors - Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (My University, 1992)
The electrical degradation phenomena of zinc oxide-based varistors were studied using a high-energy current pulse and a.c. polarization at different temperatures. Activation energy measurements during the degradation process showed that these phenomena are associated with diffusion and that the diffusion-controlling species are slower than Zn., For degradation promoted by current pulses of 8×20 μs, the Schottky potential barrier deformation was measured. A decrease in height and width of the potential barrier due to the reduction of surface states density, N s, without a significant change in donor density, N d, was observed. To explain these results, a modification of the unstable components model is proposed for the potential barrier in which the degradation is due to oxi-reduction reactions between atomic defects. These reactions promote the elimination of zinc vacancies and/or adsorbed oxygen on the grain boundaries. © 1992 Chapman & Hall.